Representing Time. Architecture, Geometry and Astronomy. International Study Day (diségno, 2022)
The International Study Day entitled Representing Time. Architecture, Geometry and Astronomy was held on March 23, 2022, at the palazzo Spada in Rome, Italy. [read more]